2013
DOI: 10.1002/fut.21641
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Bounds on Barrier Options

Abstract: This article proposes the optimal pricing bounds on barrier options in an environment where plain-vanilla options and no-touch options can be used as hedging instruments. Super-and sub-hedging portfolios are derived without specifying any underlying processes, which are static ones consisting of not only plain-vanilla options but also cash-paying no-touch options and/or asset paying no-touch options that pay one cash or one underlying asset, respectively, if the barrier has not been hit. Moreover, the prices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The exact pricing of barrier options under realistic assumptions can therefore only be achieved by numerical techniques which will include some calibration errors. Even though Brown et al (2001) and Tsuzuki (2014) showed that in the most general case model‐free bounds for prices of barrier options can be found, it is still useful to have analytical approximations where possible.…”
Section: Introductionmentioning
confidence: 99%
“…The exact pricing of barrier options under realistic assumptions can therefore only be achieved by numerical techniques which will include some calibration errors. Even though Brown et al (2001) and Tsuzuki (2014) showed that in the most general case model‐free bounds for prices of barrier options can be found, it is still useful to have analytical approximations where possible.…”
Section: Introductionmentioning
confidence: 99%